The Effect of Obesity Degree on Childhood Pulmonary Function Tests - TORUN, EMEL; Torun, EMEL; ÇAKIR, ERKAN; Cakir, ERKAN; ÖZGEN, İLKER TOLGA; OZGUC, Fatma; Ozgen, Ilker Tolga (My University, 2014)
Background: Childhood obesity has become a global epidemic. It is related to several chronic diseases such as essential hypertension, type 2 diabetes mellitus, and renal disease. The relationship between the degree of obesity and lung functions is well defined in adults, but limited information is available about the childhood period. Aims: This study aims to determine the impact of the degree of obesity on the pulmonary functions of school children and adolescents. Study Design: Cross sectional study. Methods: Included in the study were a total of 170 school children and adolescents (9-17 years old) referred to our paediatric outpatient clinic. Of these subjects, 42 were lean and non-obese (BMI % <85), 30 subjects were overweight (BMI % ˃85, <95), 34 subjects were obese (BMI % ˃95, <97), and 64 subjects were morbidly obese (BMI % ˃97). Anthropometric measurements were taken and spirometry was performed on all subjects. Forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1 ), forced vital capacity 25-75 (FEV25-75) and peak expiratory flow (PEF) were used to measure the ventilatory functions for all the subjects. Results: The groups showed no significant differences in age or gender. Despite no statistically significant differences in FEV1 , FVC, or FEV1 /FVC, there were significant reductions in PEF (p<0.001) and FEV25-75 (p<0.001) in the overweight, obese and morbidly obese subjects, when compared with those who were non-obese. Conclusion: Overweight, obese and morbidly obese children have no obstructive abnormalities compared with healthy lean subjects.